READING INTEREST LEVEL IN PRIMARY SCHOOL TEACHERS BASED ON THE IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT IN DEPOK CITY - Ova Huzaefah; Taupik Lubis (UNIVERSITAS PAKUAN, 2021)
The culture of literacy in Indonesian society has received attention and development by a lot of parties. Not only the government, even local and foreign NGOs are also heavily involved in advancing the culture of literacy of the Indonesians. However, if we observe carefully, there is no progress of literacy culture in the everyday life among Indonesians. In order to overcome this problem, the Ministry of Education and Culture is developing a school literacy movement (GLS) program to increase community literacy through formal school education. This research was conducted to determine the level of teachers’ reading interest as a result of implementing the school literacy movement program. The method used was quantitative and descriptive analysis through statistical tests. The results showed that primary school teachers in Depok City had a high category of reading interest 26.7%, medium category reading interest 44.4% and low category 28.9%. The results also showed that the implementation of GLS was found in the high category 33.3%, the medium category 43.3% and low category 23.3%. From the research results it was also known that the t-value is 10.051 and the t table is dk = n-k, dk = 90-1 = 89 at the 5% significance level, so it was known that the t table was 1.7. Based on the calculation of t value was greater than t table, namely 7.332 1.7. Therefore, it can be concluded that the School Literacy Movement Program had a significant effect on Teacher Reading Interest.